Study of La0.1Sr0.9TiO3 electrochemical response as anode for SOFC and its relation with microstructure - Tagarelli, Ernesto; Vega Castillo, Jesus Eduardo; Ortiz, Mariela Gisela; Troiani, Horacio Esteban; Chanquia, Corina Mercedes; Montenegro Hernandez, Alejandra (Elsevier Science, 2024)
Fil: Tagarelli, Ernesto. Universidad Tecnologica Nacional. Facultad Regional La Plata; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina